Behavior Differences Between Search-and-Rescue and Pet Dogs - Hare, Elizabeth; Kelsey, Kathleen M.; Serpell, James A.; Otto, Cynthia M. (Frontiers in Veterinary Science, 2018)
Behavioral traits such as trainability, fearlessness, and energy are required for dogs to succeed as urban search-and-rescue (USAR) dogs. Certification by the Federal Emergency Management Agency (FEMA) ensures that dogs and handlers have extensive training and have demonstrated specific skills in the field. To determine whether behavioral differences exist between USAR and pet dogs, and between FEMA-certified USAR and non-FEMA-certified USAR dogs, the Canine Behavioral Assessment and Research Questionnaire (C-BARQ) was administered to 129 SAR dogs participating in the post-9/11 medical surveillance study and a breed-matched sample of 2131 pet dogs. Non-parametric mixed models were fit for each C-BARQ subscale with explanatory variables USAR/non-USAR status, FEMA certification status, breed, sex, neuter status, and age. USAR dogs had higher scores for trainability (P < 0.001) and energy (P < 0.001), and lower scores for aggression toward strangers (P < 0.01), aggression and fear toward dogs (P < 0.01), fear of dogs (P < 0.001), chasing (P < 0.001), fear of strangers (P < 0.001), and non-social fear (P < 0.001) than pet dogs. FEMA-certification was associated with lower fear of dogs (P < 0.05) and separation-related issues (P < 0.01) than non-FEMA certified USAR dogs. The traits identified in this study could provide guidance for more efficient selection of candidate USAR dogs and breeding stock.